Frequency of Delayed Healing of Extraction Socket in Diabetic Patients with Different Glycemic Control - Murtaza; Dad, Fazal; Uppal, Asma; Bilal, Muhammad; Abdullah (Indus Journal of Bioscience Research, 2025)
Background: Impaired angiogenesis, weakened immune systems, and decreased collagen synthesis make delayed healing of extraction sockets in diabetic patients a prevalent clinical problem. The way diabetics manage their blood sugar levels has a big impact on how well oral surgery goes for them. Knowledge of the connection between blood glucose levels and healing can help inform postoperative care plans and clinical judgement. Objective: The objective of this study is to figure out how common delayed healing is in extraction sockets in diabetic patients and investigating the relationship between delayed healing and glycaemic control levels (good, moderate, and poor). Identifying important clinical and demographic factors that may affect wound healing results, such as gender, age, and the length of diabetes, is another goal. Methodology: A cross-sectional study was carried out at a Quetta tertiary care hospital, using random sampling to choose a sample of 120 diabetic patients. Based on their HbA1c levels, participants were divided into three glycaemic control groups: good (